Fish Waste Oil in Laying Hens* Diets - Brelaz,KCBTR (2019)
ABSTRACT The present study aimed to evaluate increasing levels of fish waste oil in laying hens diets on performance, egg quality, and sensory features of the eggs. 192 Hisex White laying hens with 29 weeks of age were used, with water and food ad libitum. The experimental design was completely randomized consisting of eight treatments corresponding to the inclusion levels of fish waste oil (0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 and 3.5%) in the diets, with four replicates of six birds each. Data collected were subjected to polynomial regression at 5% of significance. Differences (p<0.05) were observed in feed intake and egg mass. Feed intake increased until 2.50% of fish waste oil in the diets. Differences were not observed (p>0.05) in all variables analyzed. Differences were observed (p<0.05) in flavor. Eggs from birds fed diets up to 2.00% present better acceptance by the tasters. Above this level, there was a considerable drop in acceptance. From these results, the present study indicates that the use of fish waste oilin laying hens diets did not affect the egg quality. However, its high inclusion negatively affected the feed intake, egg mass, and egg flavor.